A brute-force spectral approach for wave estimation using measured vessel motions. (July 2018) - Nielsen, Ulrik D.; Brodtkorb, Astrid H.; Sørensen, Asgeir J.
Abstract: The article introduces a spectral procedure for sea state estimation based on measurements of motion responses of a ship in a short-crested seaway. The procedure relies fundamentally on the wave buoy analogy, but the wave spectrum estimate is obtained in a direct - brute-force - approach, and the procedure is simple in its mathematical formulation. The actual formulation is extending another recent work by including vessel advance speed and short-crested seas. Due to its simplicity, the procedure is computationally efficient, providing wave spectrum estimates in the order of a few seconds, and the estimation procedure will therefore be appealing to applications related to realtime, onboard control and decision support systems for safe and efficient marine operations. The procedure's performance is evaluated by use of numerical simulation of motion measurements, and it is shown that accurate wave spectrum estimates can be obtained for all wave directions in short-crested waves, taking the wave system to be composed by both wind generated sea and swell. Furthermore, the procedure is tested using full-scale motion data obtained from sea trials. Good wave estimations are achieved as compared to corresponding results from a free-floating (classical) wave buoy. Highlights: Shipboard sea state estimation ('wave buoy analogy') based on a brute-force residual spectralcalculation Little mathematical complexity High computational efficiency Inclusion of vessel advance speed Non-parametric wave spectrum estimates allowing for wind generated sea in combination with Swell